Insecticide Resistance Profile, Synergism Studies And Bait Evaluation Against Field-Collected German Cockroach, Blattella Germanica (L.) (Blattodea: Blattellidae) From Singapore - Chai , Ru Yuan (2010)
This research project focuses on the resistance profile, possible resistance mechanism and bait evaluation of German cockroaches, Blattella germanica (Linnaeus) from Singapore. Twenty-two strains of the German cockroach were collected from various localities in Singapore and their resistance levels against various commercial insecticides were determined using topical bioassay. Results revealed that insecticide resistance is prevalent in these German cockroach populations.